A preliminary study into the effect of processing on Eurycoma longifolia water extract yield - Kumaresan, Sivakumar; Sarmidi, Mohamad Roji (2003)
Eurycoma longifolia or Tongkat Ali is a traditional Malaysian herb associated with medicinal benefits such as antipyretic, anti-malarial and aphrodisiac effects. At present it has been identified as a potentially lucrative commercial product to be developed as an international product by the Malaysian government. There is therefore a need to produce Tongkat Ali water extracts of high yield and quality. A key issue in the production of herbal medicines such as Tongkat Ali is the production of extracts standardized to a specific chemical marker. At present, Tongkat Ali extracts are standardized to eurycomanone, a quassinoid which is the primary component present in the extract. Due to the varying planting conditions of Tongkat Ali plants, the concentration of the required phytochemicals within the raw material varies in quantity and quality. Thus, phytochemical extract processing methods must be developed which enhance phytochemical extraction to achieve the required phytochemical profile and yield. Varying processing conditions as well as reconstituting mixtures of extracts can be utilized to produce standardized herbal extracts. In this preliminary works, the effect of varying particle size, extraction time, and solvent ratio on the quantity of phytochemicals extracted on a laboratory scale from a single sample of Tongkat Ali was studied. It was found that increasing solvent ratio as well as extraction time increased yield. However, the effect of particle size on yield was inconclusive.